Cognitive Reserve in Parkinson’s Disease: The Effects of Welsh-English Bilingualism on Executive Function - John V. Hindle; Pamela A. Martin-Forbes; Alexandra J. M. Bastable; Kirstie L. Pye; Anthony Martyr; Christopher J. Whitaker; Fergus I. M. Craik; Ellen Bialystok; Enlli M. Thomas; Virginia C. Mueller Gathercole; Linda Clare (Parkinson's Disease)
Objective. Bilingualism has been shown to benefit executive function (EF) and delay the onset of Alzheimer’s disease. This study aims at examining whether a bilingual advantage applies to EF in Parkinson’s disease (PD). Method. In a cross-sectional outpatient cohort of monolingual English (n=57) and bilingual Welsh/English (n=46) speakers with PD we evaluated the effects of bilingualism compared with monolingualism on performance on EF tasks. In bilinguals we also assessed the effects of the degree of daily usage of each language and the degree of bilingualism. Results. Monolinguals showed an advantage in performance of language tests. There were no differences in performance of EF tests in monolinguals and bilinguals. Those who used Welsh less in daily life had better performance on one test of English vocabulary. The degree of bilingualism correlated with one test of nonverbal reasoning and one of working memory but with no other tests of EF. Discussion. The reasons why the expected benefit in EF in Welsh-English bilinguals with PD was not found require further study. Future studies in PD should include other language pairs, analysis of the effects of the degree of bilingualism, and longitudinal analysis of cognitive decline or dementia together with structural or functional neuroimaging.